Metafora Antropomorfis dalam Lirik Lagu “Kontras” karya Figura Renata - Atika Gusriani (Lingua Susastra, 2022)
Multiple interpretations are understandings that arise in various ways as a result of song lyrics that are implied so that it is difficult to interpret a song that is heard. This study aims to describe the metaphor in the lyrics of the song “kontras” by Figura Renata, focusing on anthropomorphic metaphors. This research uses descriptive research method. The data contained in this study is qualitative data consisting of words, phrases, clauses, and sentences in the form of lexicon and lexical meaning in the lyrics of the song "Kontras" by Figura Renata. The data sources in this study are the lyrics of the song "Kontras" by Figura Renata. Based on 12 data obtained from the lyrics of the song "kontras" by Figura Renata, it is concluded that six of the lyrics of the 12 song lyrics contain Anthropomorphic Metaphors. The lyrics of the song include jokes on the third line; heartbeat in the fourth row; furious on the fifth line; profuse blood in the eighth row; netra on the ninth row; lament on the twelfth line.